2016
DOI: 10.7448/ias.19.1.20627
|View full text |Cite
|
Sign up to set email alerts
|

In the interests of time: improving HIV allocative efficiency modelling via optimal time‐varying allocations

Abstract: IntroductionInternational investment in the response to HIV and AIDS has plateaued and its future level is uncertain. With many countries committed to ending the epidemic, it is essential to allocate available resources efficiently over different response periods to maximize impact. The objective of this study is to propose a technique to determine the optimal allocation of funds over time across a set of HIV programmes to achieve desirable health outcomes.MethodsWe developed a technique to determine the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…We expect this limitation to most affect funding for VMMC in generalized epidemic settings, as shown by Shattock et al 24 for South Africa. Seventh, for the optimization scenario whereby international funds were permitted to be shifted between countries, we assumed that redistribution would not be limited to investment in select programme(s), as is often specified by some funding organizations.…”
Section: Discussionmentioning
confidence: 82%
“…We expect this limitation to most affect funding for VMMC in generalized epidemic settings, as shown by Shattock et al 24 for South Africa. Seventh, for the optimization scenario whereby international funds were permitted to be shifted between countries, we assumed that redistribution would not be limited to investment in select programme(s), as is often specified by some funding organizations.…”
Section: Discussionmentioning
confidence: 82%
“…The methods we have developed and employed in this paper are based on the mathematics of control theory that has been used to address epidemiological resource allocation problems since the 1970s [ 6 ]. However, much of the research applying control theory to epidemiologic problems has focused on purely theoretical concerns [ 7 9 ], calculated the optimal allocation strategy for very general settings [ 10 16 ], or assumed a strong a priori form to the control [ 17 ]. Studies where the underlying model and choice of parameters were tailored to a specific setting [ 18 , 19 ] were less frequent than general studies.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, other modelling studies suggests that immediate rapid expansion of efforts, particularly until 2020, will be critical to meeting the goal of ending the epidemic by 2030 . At the national level, modelling studies have also found that intensifying investment in prevention and treatment immediately will be most impactful . Intensifying the response is critical as the large and growing treatment costs are, in some places, already at the same scale as national debt, with needs exceeding the projected HIV fiscal space in the long‐term .…”
Section: Resultsmentioning
confidence: 99%